VIth World Congress on Science and Football, Book of Abstracts, January 16-20, 2007, Antalya, Turkey - Poster Presentations - Referee and Rules (Journal of Sports Science & Medicine, 2007)
Summaries on the following topics: P-146 Analysis of between-half work rates in English Premier League soccer referees P-147 Interpretation and application of the laws of the game in football incidents leading to player injuries P-148 Offside decision-making process in association football using recall paradigm P-149 Job satisfaction in Turkish football referees P-150 Deconstructing referee P-151 A research on sprint and vertical jump capabilities of professional football league referees in Turkey P-152 Career development of youth football players in J-League Academy: Case of career formation and career orientation P-153 Analysis of strategic planning in Asian institute of rugby